Dampak Pandemi COVID-19 Terhadap Tingkat Kesejahteraan Penduduk di Provinsi Maluku Utara - Insaf Santoso (PT FORMOSA CENDEKIA GLOBAL, 2022)
The COVID-19 pandemic that has hit Indonesia since March 2020 until now has had a fairly large impact. From a macro perspective, BPS reported that there was a contraction in economic growth, an increase in the number of poor people and unemployment resulting in a decline in the level of welfare of the population. North Maluku Province also experienced a similar problem, namely a decline in the level of population welfare as measured by per capita household expenditure. To identify the pattern of decline, descriptive statistical analysis is used based on Susenas panel data for the March-September 2020 period. The results of the analysis show that the COVID-19 pandemic has had an unfavorable impact on per capita expenditure. The characteristics of the households that are significantly affected are those who live in urban areas. In this region, the largest decline occurred in those with the status of informal workers and the elderly.